PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM POS KEADILAN PEDULI UMMAT (PKPU) DI PASAR LALANG KELURAHAN KURANJI KOTA PADANG - Beni Putra Hanafi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The definition of poverty is very diverse, ranging from just the inability to fulfill basic needs and improve conditions to a broader understanding that includes social and moral components. The purpose of this study was to analyze the process of Community Empowerment through the PKPU Program in Pasar Lalang, Kuranji Village, Padang City. The usefulness of this research is to reveal the process of community empowerment through the PKPU program at Pasar Lalang, to find out how far the empowerment process carried out by PKPU Kota Padang in empowering the Lalang Market community in accordance with the concepts of empowerment. This research is in the form of qualitative descriptive, namely presenting facts and symptoms in the field and then analyzed so that the final conclusions are clearly understood. In collecting data the author uses the method of interview, observation and documentation. Based on the results of the study obtained several facts seen from various things. First seen from the process of liberation and awareness carried out by PKPU, the realization was in the form of socialization and enlightenment in the form of lectures held at mosques and open fields that had been prepared in advance. Pasar Lalang community is given the motivation to be able to change their lives for the better. After that PKPU socialized the programs they will provide to the community.